Refinement of the Sugar Puckering Torsion Potential in the AMBER DNA Force Field - Zgarbová, Marie; Šponer, Jiří; Jurečka, Petr (Journal of chemical theory and computation, 2025)
The transition from B-DNA to A-DNA occurs in many protein-DNA interactions or in DNA/RNA hybrid duplexes, and thus plays a role in many important biomolecular processes that convey the biological function of DNA. However, the stability of A-DNA is severely underestimated in current AMBER force fields such as OL15, OL21 or bsc1, potentially leading to unstable or deformed protein-DNA complexes. In this study, we refine the deoxyribose dihedral potential to increase the stability of the north (N) puckering present in A-DNA. The new parameters, termed OL24, model A/B equilibrium in B-DNA duplexes in water in good agreement with nuclear magnetic resonance (NMR) experiment. They also improve the description of DNA/RNA hybrids and the transition of the DNA duplex to the A-form in concentrated ethanol solutions. These refinements significantly improve the modeling of protein-DNA complexes, increasing their structural stability and A-form population, while maintaining accurate representation of canonical B-DNA duplexes. Overall, the new parameters should allow more reliable modeling of the thermodynamic equilibrium between A- and B-DNA forms and the interactions of DNA with proteins.
Keywords: A-DNA; DNA, B-Form; DNA; Thermodynamics; termodynamika; Molecular Dynamics Simulation; konformace nukleové kyseliny; Nucleic Acid Conformation; simulace molekulární dynamiky; DNA, A-Form; B-DNA; Deoxyribose; deoxyribosa